Systems ideologies and street-level bureacrats: policy change and perceptions of quality in a behavioral health case system - Isett, Kimberly Roussin; Topping, Sharon; Morrissey, Joseph P. (2006)
This article examines the stability of street-level bureaucrats' negative perceptions regarding a newly implemented managed care system as quality of care and service delivery in a publicly funded behavioral health care system. Overall findings indicate that the generally negative perception of managed care did not differ between staff in the two programs, indicating a weak effect on attitudes of frontline workers. More proximal variables to the caregiver, such as service type and job title, show more influence on attitudes. The conclusion discusses the implications of these findings for practicing administrators and academic researchers. - Reproduced.
Keywords: Health services; Civil service